Preparing of Nano-Hydroxyapatite from Seashell and Mixed with Gold to Repair Bony Defect of Mandibular Bone in Rabbits - Ghada A. Taqa; Banan N. Al-Hussary; Nazhan Th. Kashmola (Iraqi Journal of Industrial Research)
The objectives of the present study were undertaken to prepared hydroxyapatite powder from seashell and convert this to nano size and then added to gold nanoparticles. Materials and Methods: The seashells was cleaned and the phosphoric acid was added. The product was inserted in oven then calcined in the muffled furnace, to evaporate CO2 and getting the white crystalline powder which indicated presence of hydroxyapatite. This powder was converted to nanoparticle. Gold 1% mixed with prepared seashell nano hydroxyapatite. The characteristics of the prepared nano hydroxyapatite from seashell, were studied by the FTIR infrared spectrophotometer. The most biocompatible nano hydroxyapatite estimation by chemical test and examine prepared nano hydroxyapatite from seashell alone or when mixed with gold 1% in vivo to detect the effectiveness on reparing bone defect in mandibulare rabbits. Results: The results of an infrared measurement (FTIR Spectroscopy) for prepared nano hydroxyapatite showed that the chemical structure and band have the same FTIR spectrum of standard nano hydroxyapatite and have the same nano traits as the chemical test showed a yellow precipitation consisting in the nHA seashells. As an indication of biocompatibility and increase Bone Mineral Density by repairing bone defect in rabbits. And when added gold to nano hydroxyapatite, increased the efficacy of bone remodeling and repair bone. Conclusions: The possibility of preparing nanoparticles for hydroxyapatite from seashell are simple and inexpensive feedstock's and can be successfully produced by chemical precipitation technology from seashells with a phosphoric acid solution.